2020
DOI: 10.5296/jas.v8i1.16093
|View full text |Cite
|
Sign up to set email alerts
|

Cephaleuros virescens in Brazilian Mahogany: Algae Parasitic Disease Threatening an Important Reforestation Tree

Abstract: The forest species are frequent targets of diseases. In this context, the plant-parasitic algae comprise a separate group in this process, including the algae genus Cephaleuros, which attacks mahogany cultivars. The objective of this work was to accomplish the molecular and morphological characterization of the causal agent of algae spots occurring in Brazilian mahogany (Swietenia macrophylla). Somatic and reproductive algae structures contained in lesions on the leaves had the DNA extracted and amplified by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…However, based on the result of morphological characteristics, the measurements of sporangium and sporangiophore of the algae species are 20. 6-41.32 × 20.6 and 237.62-464.85 ×15.5 respectively in this study and are found to be close to C. virescence identified by Pereira et al (2020) from Swietenia sp., Malagi et al (2011) from Ficus benghalensis and Han et al (2011) from Citrus sinensis. However, these measurements, are in contrary, different mainly in the length of sporangiophore, to Cephaleuros parasiticus, obtained by Ponmurugan et al (2010) (Chanthapatchot and Satjarak, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…However, based on the result of morphological characteristics, the measurements of sporangium and sporangiophore of the algae species are 20. 6-41.32 × 20.6 and 237.62-464.85 ×15.5 respectively in this study and are found to be close to C. virescence identified by Pereira et al (2020) from Swietenia sp., Malagi et al (2011) from Ficus benghalensis and Han et al (2011) from Citrus sinensis. However, these measurements, are in contrary, different mainly in the length of sporangiophore, to Cephaleuros parasiticus, obtained by Ponmurugan et al (2010) (Chanthapatchot and Satjarak, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…In this study, coefficients variation 42% for sporangiophore length and 30% for that of sporangia were observed. These results show that the sporangiophores length is more variable when compared with other structures measured (Pereira et al, 2020). Finally, it is worth noting that the homogeneity obtained in the measurement of micromorphological structures helps the characterization and standardization of C. virescens structure measurement (Carvalho et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations